2013
DOI: 10.1093/ndt/gft408
|View full text |Cite
|
Sign up to set email alerts
|

Collapsing glomerulopathy superimposed on diabetic nephropathy: insights into etiology of an under-recognized, severe pattern of glomerular injury

Abstract: CG contributes to an increased level or new onset of proteinuria in DN which may be intractable. CG in DN with advanced vascular hyalinosis is presumably due to ischemic podocyte injury and is of prognostic significance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 28 publications
3
30
0
1
Order By: Relevance
“…We did not observe an association between mesangiolysis or hyalinosis with EXHC (data not shown). Salvatore et al 20 described a series (n=26) of HIV-negative patients with diabetes and collapsing glomerulopathy with epithelial proliferation in Bowman's space (pseudocrescents), virtually identical to the EXHC observed in our study. They propose that severe arteriolosclerosis leads to hypoxic injury to podocytes and resultant collapse of the glomerular tuft.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…We did not observe an association between mesangiolysis or hyalinosis with EXHC (data not shown). Salvatore et al 20 described a series (n=26) of HIV-negative patients with diabetes and collapsing glomerulopathy with epithelial proliferation in Bowman's space (pseudocrescents), virtually identical to the EXHC observed in our study. They propose that severe arteriolosclerosis leads to hypoxic injury to podocytes and resultant collapse of the glomerular tuft.…”
Section: Discussionsupporting
confidence: 83%
“…18 Additional features not included in the RPS scoring are segmental sclerosis (SS) and extracapillary hypercellularity (EXHC), which have been noted in patients with diabetes and may have prognostic importance. [19][20][21] We postulated that the RPS Diabetic Nephropathy Classification does not include several glomerular parameters that could be useful for phenotyping and prognosticating the clinical course for DKD. The objectives of these analyses were to: (1) provide a detailed characterization of light microscopic pathologic lesions in clinical biopsy specimens with diabetic glomerulosclerosis; and (2) quantify the risk for diabetic ESRD according to individual nephropathologic lesions and determine which are independently associated with the risk for ESRD.…”
mentioning
confidence: 99%
“…Furthermore, in the presence of hyperglycemia, mesangial cells express renin and angiotensinogen (52) that stimulates increased production of TGF-β and VEGF-A in podocytes, resulting in augmented thickening of the extracellular matrix and higher rates of podocyte apoptosis (5355). Clinical cases of DN carry the risk of collapsing glomerulopathy, which is characterized by expansion of the glomerular basement membrane, capillary wall deformation, and epithelial cell proliferation, all of which are associated with an overexpression of glomerular VEGF-A (5658). Collectively, the progressive changes of DN include increased proteinuria, the fusion of podocyte foot processes, and alterations in glomerular endothelial cell proliferation and maintenance that have all been identified both in humans and multiple animal models (59).…”
Section: Role Of Vegf In Diabetic Nephropathymentioning
confidence: 99%
“…Also, glomerular epithelial hyperplasia can become particularly florid, appearing as crescentic glomerulonephritis. This particular difficulty is often encountered on a background of membranous glomerulopathy, diabetic glomerulopathy, or membranous lupus nephritis or TMA, further complicating interpretation [30, 31, 47]. As no data exist detailing any specific test to differentiate crescents from CGP this formidable question is often relegated to experience and opinion.…”
Section: The Difficult Diagnosis; Entities Mimicking Cgpmentioning
confidence: 99%
“…In the case of underlying diabetic glomerulopathy, Salvatore et al . have recently addressed the question of collapsing lesions superimposed on diabetic glomerulopathy (Figure 1T) and their study suggested that these lesions might be attributable to ischemia [47]. Similarly, CGP in TMA is thought to be due to ischemia.…”
Section: The Difficult Diagnosis; Entities Mimicking Cgpmentioning
confidence: 99%